Diameter-specific growth of single-walled carbon nanotubes using tungsten supported nickel catalysts. (July 2017) - Li, Meihui; Yang, Feng; Ding, Li; Liu, Xiyan; Zhang, Zeyao; Zhang, Daqi; Zhao, Xiulan; Yang, Juan; Li, Yan
Abstract: We developed a W/WOx -supported Ni catalyst for the diameter-controlled growth of single-walled carbon nanotubes (SWNTs) by chemical vapor deposition (CVD) valid for different substrates and broad growth conditions. The Ni nanoparticles anchored on W/WOx are well dispersed and show superior stability to high temperature. Under broad CVD windows of temperature and carbon feedstock supply conditions, SWNTs with narrow diameter distribution of ∼1.3 ± 0.1 nm can be steadily synthesized. This strategy also works well in the growth of surface lattice oriented SWNT arrays. The aligned SWNTs grown on ST-cut quartz show similar diameters to those obtained on silicon wafers. Graphical abstract: